Sustainable Future of International Trade and Environmental Governance in ASEAN: Indonesia’s Economic Growth and Green Commitments - Abdi Reviane, Indraswati Tri; Paddu, Abdul Hamid; Djam'an, Fitriwati; Idris, Aditya; Wasiaturrahma, Wasiaturrahma (International Journal of Energy Economics and Policy, 2026)
This study investigates the determinants of sustainable development in Indonesia, with a specific focus on reconciling economic growth and international trade with environmental governance and green commitments. The research aims to empirically test the Environmental Kuznets Curve (EKC) hypothesis and evaluate the distinct roles of governance quality and renewable energy. Utilizing data from 1990–2022, the methodology employs second-generation econometric techniques robust to cross-sectional dependence, including the Cross-sectionally Augmented ARDL (CS-ARDL) model to estimate long-run and short-run dynamics. The findings confirm the EKC hypothesis for Indonesia, revealing an inverted U-shaped relationship between income and CO₂ emissions. More significantly, the results establish that robust government governance and the adoption of renewable energy are critical, statistically significant drivers in mitigating environmental degradation, with the economy showing a rapid adjustment speed to long-run equilibrium. The study’s implications stress the necessity for integrated policies that strengthen institutions and accelerate the energy transition. Its novelty lies in its dual-focused analysis and robust methodology, offering a nuanced and actionable framework for sustainable growth in ASEAN’s largest economy, demonstrating that effective governance is a fundamental enforcer of green commitments.